Sikap Keuangan, Kontrol Perilaku, Efikasi Diri dan Perilaku Keuangan - Eka Yusnita Nila Sari; A. Khoirul Anam (Universitas Winaya Mukti, 2021)
The practice of personal financial management among young people is currently getting serious attention, including among students. The problem is based on the implementation of basic financial knowledge which is still minimal. The development of good financial behaviour in students requires special attention because aspects of financial behaviour have a significant influence on their lives after graduating. This study aims to determine the effect of financial attitudes, behavioral control, and self-efficacy on financial behaviour. The type of research carried out is quantitative with primary data through a structured questionnaire. The research sample was selected from one college student with a total of 75 respondents. The sampling technique was purposive sampling on active status students and had completed the Financial Management course. This research is based on The Theory of Planned Behaviour (TPB). The results revealed that financial attitudes and self-efficacy affected financial behaviour, while behavioral control did not affect financial behaviour. Good financial behaviour helps improve financial well-being where positive financial behaviour is associated with positive life outcomes